THE MODERN PRACTICES OF CORPORATE SOCIAL POLICY IN RUSSIAN COMPANIES - I. V. Dolgorukova (Vestnik MGIMO-Universiteta, 2014)
In this work the author proposes an interpretation of the corporate social policy as one of the most important areas of a company business which is designed to develop an effective interaction between a company, a society and a state. The author has analyzed the main social practices of realization of a company corporate social policy. A research on the problems and models of social activity of companies makes it possible to reveal the basic components, the specificity, to disclose the role of the corporate policy in the process of establishing Russia as a social state, and to determine the principal factors of formation of the corporate social responsibility as a social institution. In the scientific article author analyses the social practices of forming of reputation of the Russian companies. Social reputation is understood as one of indexes of efficiency of corporate policy. Article contains information on results of author's sociological research of a condition of corporate social policy and the factors of development at large and medium-sized enterprises of the country. During research the priority directions of development of corporate social policy at the modern Russian enterprises were analysed, the comparative analysis of estimates of employees and heads of the enterprises was carried out. In conclusion, the author states the thesis that the understanding of the main directions of corporate social policy shouldn't be limited to inclusion in it only civil and legal liability of the businessman. Business as social institute is the most important social and economic subject of the Russian society. Unfortunately, it isn't quite realized by businessmen. Sociological research showed that corporate social policy is understood by them generally as responsibility before hired employees of the enterprise. This article can be useful for governmental specialists designing the business policy, for entrepreneurs, academics, postgraduates and undergraduates, as well as for a wide range of readers.